Evidence mapping of preference elicitation for non-pharmaceutical interventions targeting respiratory viral transmission: A scoping review protocol - Hui Yee Yeo; Ji Yeon Park; Samantha Marsh; Lorraine Castelino; Nikki Turner (PLoS ONE, 2026)
Introduction Non-pharmaceutical interventions (NPIs) such as mask use, physical distancing, business or school closure, and isolation have been central to controlling respiratory viral infections, including influenza, COVID-19, and respiratory syncytial virus (RSV). Understanding the preferences of the public and stakeholders for these interventions is critical to ensure their acceptability, uptake, and effectiveness. Discrete choice experiments (DCEs) provide a robust method to quantify how individuals value different attributes of NPIs and the trade-offs they are willing to make. However, evidence from DCEs is fragmented across diseases, populations, and methodological approaches. This scoping review aims to systematically map and synthesise evidence from DCEs examining public and stakeholder preferences for NPIs used in the prevention and control of influenza, COVID-19, and RSV. Specifically, it will: (1) summarise the attributes and attribute levels used in DCEs, and the methods employed to select them; and (2) identify which NPI attributes are most valued by the public and key stakeholders, including patients, healthcare workers, and policymakers. Methods and analysis The review will follow the PRISMA-ScR framework. Comprehensive searches of electronic databases (PubMed, Scopus, and Embase) will identify DCEs evaluating NPIs for influenza, COVID-19, and RSV. Data extraction will capture study characteristics, target populations, attributes, experimental design, and analytical methods. Reporting quality will be appraised using the DIRECT Checklist. Given anticipated heterogeneity, findings will be synthesised narratively. By providing a structured overview of existing DCE evidence, this review will inform the design of future preference studies and guide the development of acceptable and evidence-based NPI strategies for respiratory viral infections. Ethics and Dissemination No ethical approval is required. The completed review will be shared through peer-reviewed journals and conference presentations. Open Science Framework Registration https://doi.org/10.17605/OSF.IO/H36UC